Bioassay‐Guided Isolation and Structural Modification of the Anti‐TB Resorcinols from Ardisia gigantifolia. (26th April 2016) - Guan, Yi‐Fu; Song, Xun; Qiu, Ming‐Hua; Luo, Shi‐Hong; Wang, Bao‐Jie; Van Hung, Nguyen; Cuong, Nguyen M.; Soejarto, Djaja Doel; Fong, Harry H.S.; Franzblau, Scott G.; Li, Sheng‐Hong; He, Zhen‐Dan; et al.
Abstract : Tuberculosis (TB) is a highly contagious disease mainly caused by Mycobacterium tuberculosis H37 RV . Antitubercular (anti‐TB) bioassay‐guided isolation of the CHCl3 extract of the leaves and stems of the medicinal plant Ardisia gigantifolia led to the isolation of two anti‐TB 5‐alkylresorcinols, 5‐(8 Z ‐heptadecenyl) resorcinol (1 ) and 5‐(8 Z ‐pentadecenyl) resorcinol (2 ). We further synthesized 15 derivatives based on these two natural products. These compounds (natural and synthetic) were evaluated for their anti‐TB activity against Mycobacterium tuberculosis H37 RV . Resorcinols1 and2 exhibited anti‐TB activity with MIC values at 34.4 and 79.2 μ m in MABA assay, respectively, and 91.7 and 168.3 μ m in LORA assay, respectively. Among these derivatives, compound8 was found to show improved anti‐TB activity than its synthetic precursor (2 ) with MIC values at 42.0 μ m in MABA assay and 100.2 μ m in LORA assay. The active compounds should be regarded as new hits for further study as a novel class of anti‐TB agents. The distinct structure–activity correlations of the parent compound were elucidated based on these derivatives. Abstract : We have identified two antitubercular (anti‐TB) 5‐alkylresorcinols, 5‐(8 Z ‐heptadecenyl) resorcinol (1 ) and 5‐(8 Z ‐pentadecenyl) resorcinol (2 ) through bioassay‐guided separation from the leaves and stems of the medicinal plant Ardisia gigantifolia, and further synthesized 15 derivatives (3 ‐17 ) based on these two natural products. These compounds were evaluated for their anti‐TB activity against Mycobacterium tuberculosis H37 RV .